May a unitary autonomic index help assess autonomic cardiac regulation in elite athletes? Preliminary observations on the national Italian Olympic committee team - Sala, R.; Malacarne, M.; Tosi, F.; Benzi, M.; Solaro, N.; Tamorri, S.; Spataro, A.; Pagani, M.; Lucini, D. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Long term endurance training, as occurring in elite athletes, is associated to cardiac neural remodeling in favor of cardioprotective vagal mechanisms, resulting in resting bradycardia and augmented contribution of cardiac parasympathetic nerve activity. Autonomic assessment can be performed by way of heart rate variability. This technique however provides multiple indices, and there is not yet complete agreement on their specific significance. Purpose of the study was to assess whether a rank transformation and radar plot could provide a unitary autonomic index, capable to show a correlation between intensity of individual work and quality of autonomic regulation.